The carrot seed - Krauss, Ruth; Johnson, Crockett, 1906-1975 (New York : HarperCollins, 1945)
Even when his family teases him, a little boy persists in his belief that a plant will grow from the seed he planted.
05-08.
K-3.
AD400L
Decoding demand: 83 (very high) Semantic demand: 28 (low) Syntactic demand: 72 (high) Structure demand: 45 (medium)
Lexile
Accelerated Reader
Keywords: Seeds -- Juvenile fiction; Gardening -- Juvenile fiction